DIDACTIC POTENTIAL OF VIRTUAL REALITY TECHNOLOGIES IN TEACHING HUMAN ANATOMY (World Bulletin of Public Health, 2025)
The integration of virtual reality (VR) technologies into medical education represents a significant advancement in the teaching of human anatomy. Traditional methods of anatomy instruction, which rely heavily on cadaver dissection and textbook illustrations, are increasingly being supplemented or replaced by immersive digital tools. This article explores the didactic potential of VR technologies in enhancing anatomical understanding, spatial orientation, and student engagement. Through analysis of recent studies and educational case models, the paper highlights how VR provides interactive 3D visualization, repeatable practice environments, and individualized learning experiences. The use of VR in anatomy education not only improves retention of knowledge but also addresses ethical, logistical, and financial challenges associated with conventional teaching methods. This technological shift paves the way for a more effective, safe, and student-centered medical curriculum